Review and Prospects of PEM Water Electrolysis at Elevated Temperature Operation - Bonanno, Marco; Müller, Karsten; Bensmann, Boris; Hanke-Rauschenbach, Richard; Aili, David; Franken, Tanja; Chromik, Andreas; Peach, Retha; Freiberg, Anna T.S.; Thiele, Simon (Advanced Materials Technologies, 2023)
Polymer electrolyte membrane water electrolyzers (PEMWE) are currently restricted to an operating temperature range between 50 to 80 °C. This review shows that elevated temperature (ET) above 90 °C can be advantageous with respect to i) reduced cell voltages, ii) a reduction of catalyst loading or possibly the employment of less noble electrocatalysts, and iii) a greater potential for waste heat utilization when the electrolyzer is operated in exothermal mode (when the cell voltage is higher than the thermoneutral voltage). Together with presenting an overview of the materials and components utilized in elevated temperature PEMWE under liquid and steam operation, this article summarizes the experimental and modeling performances reported to date, highlights the challenges ahead, and suggests aspects, which will need to be considered to improve the performance at elevated temperature. Key points, which arise from this work are the extensive need of re-assessing the material selection both for the cell components and also at a system level, the effects and optimization of working with steam operation, and in the long run, the need for techno-economic analyses to ultimately assess whether efficiency gains will truly translate to a cost-effective technology alternative.
CRIS-Team Scopus Importer:2023-12-29
Keywords: elevated temperature; PEM water electrolysis